Infant Formula Supplemented with Biotics: Current Knowledge and Future Perspectives - Seppo Salminen; Bernd Stahl; Gabriel Vinderola; Hania Szajewska (MDPI, 2022)
Breastfeeding is natural and the optimal basis of infant nutrition and development, with many benefits for maternal health. Human milk is a dynamic fluid fulfilling an infant's specific nutritional requirements and guiding the growth, developmental, and physiological processes of the infant. Human milk is considered unique in composition, and it is influenced by several factors, such as maternal diet and health, body composition, and geographic region. Human milk stands as a model for infant formula providing nutritional solutions for infants not able to receive enough mother's milk. Infant formulas aim to mimic the composition and functionality of human milk by providing ingredients reflecting those of the latest human milk insights, such as oligosaccharides, bacteria, and bacterial metabolites. The objective of this narrative review is to discuss the most recent developments in infant formula with a special focus on human milk oligosaccharides and postbiotics.